Pengaruh Store Atmosphere, Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Pizza Hut Cabang Gatot Subroto Denpasar - Purnama Putra, I Made Bayu; Wimba, I Gusti Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
This study aims to analyze the effect of store atmosphere, product quality, and service quality on customer satisfaction of Pizza Hut cabang Gatot Subroto in Denpasar. The number of samples obtained using Slovin calculations A total of 100 respondents using Accidental Sampling method. Data collection is done through questionnaires. Then the data were analyzed using SPSS version 22, with quantitative analysis which included validity and reliability tests, classic assumption tests, multiple linear regression analysis, coefficient of determination, hypothesis testing with F test and t test. The result of hypothesis testing shows that: (1) store atmosphere has a positive and significant to customer satisfaction,(2) product quality has positive effect but not significant to customer satisfaction, (3) service quality has a positive and significant to customer satisfaction, (4) store atmosphere, product quality, and service quality has a positive and significant to customer satisfaction.